Debesų kompiuterija: darbas, bendradarbiavimas ir komunikacija. Ar debesis tenkina studentų ir mokslininkų poreikius? - Pečeliūnaitė, Angelė (Information & Media, 2011)
Informacinės komunikacinės technologijos sparčiai vystosi ir tobulėja. Debesų kompiuterija (Cloud Computing) yra dar viena naujovė, sparčiai pradėjusi plisti XXI a. pradžioje. Debesų kompiuterija – tai galimybė naudotis kompiuterine ir programine įranga internete ir mokėti tik už tai, kiek teikiama paslauga buvo pasinaudota. Debesų kompiuterijos paslaugos pirmiausia buvo orientuotos į verslą. Šio straipsnio tikslas – apžvelgti debesų technologijas ir jų teikiamas galimybes akademinei bendruomenei – studijoms, mokslui, bendradarbiavimui ir mokslinei komunikacijai. Analizuojamos trijų korporacijų siūlomos paslaugos, kreipiant dėmesį į paslaugų įvairovę, galimybes rengti projektus, konferencijas etc., technologijos saugumą, mobilumą ir paslaugų kainą. Tyrimo išvadose pabrėžiama, kad debesų kompiuterija yra patraukli mokslui ir studijoms. Debesį galima panaudoti studijoms, moksliniam darbui, bendradarbiavimui ir mokslinėje komunikacijoje, tik svarbu pasirinkti poreikius tenkinantį atitinkamą debesį. Pagrindiniai žodžiai: debesų technologijos, debesų kompiuterija, viešas ir privatus debesis, virtualus privatus tinklas, SaaS, PaaS, IaaS, virtualizacijos procesai, duomenų centrai, Microsoft Office 365, Microsoft Web Apps, Zoho debesis, Google Apps studijoms, mokslo komunikacija. Cloud Computing: The job, co-operation and communication Does Cloud Meet the Needs of Students and Scholars? Angelė Pečeliūnaitė Summary The information and communication technologies are rapidly evolving and progressing. Cloud computing is one of the innovations that began rapidly spreading from the beginning of the 21st century. The article summarizes the cloud computing paradigm, an introduction to cloud computing platforms, the cloud service offered by the cloud providers, and highlights the attractive features of this technology. The collaboration and communication methods in the cloud are discussed. The cloud computing services were primarily focused on business. The aim of the article is an overview of the cloud technologies and opportunities for the academic community – in studies, research, col-laboration and scientific communication. Delic divides research into three significant periods: empirical, theoretical, and experimental/simulation (Delic et al., 2010, p. 3). This article falls within the third study phase: an experimen-tal study comparing the services of three selected cloud providers. We analyze the cloud services of Zoho Web Apps, Microsoft Web Apps and Google Apps for Education according to the selected five categories (information gathered from web sites and company experts speaking): education in a variety of services offered working with documents and projects, scientific communication and col-laboration, data protection, mobility and price. The results have shown that cloud services are attractive to the educational community. The largest variety of service diversity and performance improvements are offered by the Microsoft and Zoho clouds on the SaaS and PaaS platforms. Zoho is a leader of these cloud services. The most attractive environment for scientific communication and collaboration (including mobility) is the Microsoft cloud. Data protection takes care of all service providers: SLA of 99.9% guarantee. Zoho uses web encryption for 256-bit SSL, and Microsoft 128-bit SSL / TSL. Google Apps for Education is in many ways behind the above-mentioned corporations, while Google’s cloud services are offered to meet students’ needs; services are provided free of charge. The investigation was conducted in December 1–15, 2010.